Examining the Relation of Productivity and Competitive Factors with Market Sales and R (Global Journal of Management and Business Research, 2015)
The present study covers empirical research on selected Agri-Biotech firms of Punjab. The sample has been chosen from state of Punjab covering sectors Food Process Industry, Fertilizer and Pesticides Industry. The study tries to identify factors influencing productivity. These factors are Internal and External Environment; Cost Efficiency; Production Planning and Control; Technological Advancement. On the basis of factor analysis the study has also identified key factors influencing competitiveness. These are Threat of new competition; Threat of substitute products or services; Bargaining power of suppliers; Intensity of competitive rivalry; Bargaining power of customers; Rivalry among existing firms. The study also tries to evaluate the findings on the basis of author-factor matrix.
Keywords: production planning and control; bargaining power; internal and external environment; agri-biotech